Structurally Diverse Polyketides From the Mangrove-Derived Fungus Diaporthe sp. SCSIO 41011 With Their Anti-influenza A Virus Activities - Luo, Xiaowei; Yang, Jie; Chen, Feimin; Lin, Xiuping; Chen, Chunmei; Zhou, Xuefeng; Liu, Shuwen; Liu, Yonghong (Frontiers in Chemistry, 2018)
Influenza A virus (IAV) is a severe worldwide threat to public health and economic development due to its high morbidity and mortality. Marine-derived fungi have been evidenced as a prolific source for the discovery of pharmacologically-active lead compounds. During the course of our search for novel bioactive substances from marine microorganisms, six new polyketides, including two octaketides (1‒2), one chromone derivative (13), two highly substituted phthalides (17‒18), and one α-pyrone derivative (21) along with 22 known congeners were isolated from a mangrove-associated fungus Diaporthe sp. SCSIO 41011. Their structures were determined by spectroscopic analysis and by comparison with literature data. And the absolute configurations were established according to the specific rotation or electron circular dichroism method. Antiviral evaluation results revealed that compounds 14, 15, 26, and 5-chloroisorotiorin displayed significant anti-IAV activities against three influenza A virus subtypes, including A/Puerto Rico/8/34 H274Y (H1N1), A/FM-1/1/47 (H1N1), and A/Aichi/2/68 (H3N2), with IC50 values in the range of 2.52‒39.97 μM. The preliminary structure-activity relationships (SARs) are also discussed. These findings expand the chemical and bioactive diversity of polyketides derived from the genus Diaporthe, and also provide a basis for further development and utilization of chromone, xanthone, and chloroazaphilone derivatives as source of potential anti-viral chemotherapy agents.